The essence and legal nature of the refusal to institute criminal proceedings - Зезюлин, Виталий Викторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article deals with the refusal to initiate criminal proceedings as a separate element of the Belarusian criminal procedural law, is determined by its nature, legal nature, importance, goals, objectives. Consideration of this issue in the future, will determine the possible directions of development of the refusal to institute criminal proceedings in the context of the evolution of the Belarusian criminal procedural law. The refusal to initiate criminal proceedings has the goals, objectives, regulated remedial order. The refusal to initiate criminal proceedings is a "filter". He avoids conducting the investigation if it is not needed. This is due to the end of the application or report a crime and the termination of criminal procedure relations. Therefore, the purpose of the refusal to initiate criminal proceedings is to stop the body's activities, carry out checks on materials, if there is reason to. For immediate tasks refusal to initiate criminal proceedings include: the prevention of illegal and groundless institution of criminal proceedings; preventing unjustified suspicions, accusations and criminal prosecution of innocent persons; identification of the causes and conditions of committing crimes; the impact on the person who committed the crime without criminal prosecution. These objectives are not exhaustive and are derived directly from the overall objectives of the criminal proceedings under Art. 7 Code of Criminal Procedure. In the article the discussion the question of finding the refusal to institute criminal proceedings in the legal system. The refusal to open a criminal case has the features of a legal institution: the union of the law, certain social relations. For this reason, the author of the article concludes that the refusal to initiate criminal proceedings is subinstitution law. This allows us to offer the author's failure wording of the criminal case, which is an independent subinstitution criminal procedural law, which on the basis of set of rules laid down in the Criminal Procedure Act, regulates the activity of the body of inquiry, the head of the investigative division of the investigator and prosecutor for the imposition of the same name resolution , due to the presence of circumstances precluding criminal proceedings during the audit by the statements and reports of crimes. The author proposed to introduce in Article 6 of the Code of Criminal Procedure for the hours 22 marked with one of the following terms: "the refusal to institute criminal proceedings - Procedural decision of the inquiry body, the head of the investigative unit of the investigator or the prosecutor, issued as a result of consideration of applications and reports of crimes in the absence of. grounds under Art. 167 of this Code". In order to address the identified inconsistencies standards Code of Criminal Procedure, the author proposes a new version of h. 1 tbsp. 178 Criminal Procedure Code of the Republic of Belarus: "If there were no grounds for criminal prosecution body of inquiry, the head of the investigative unit, the investigator, prosecutor shall make a reasoned decision on the refusal to institute criminal proceedings." In conclusion, the author concludes that the refusal to open a criminal case should be seen as a means of implementing the rights and freedoms of citizens. This will determine the possible directions of development of the refusal to initiate criminal proceedings.